Філософія правосуддя як напрям філософії права - Бігун, В.С. (Часопис Київського університету права, 2009)
Философское осмысление правосудия методологически проводится через осмысление философии правосудия как прикладной философии права. В основе предлагаемых подходов к осмыслению философии правосудия - определеное понимание философии права, которое формирует, соответственно, определенную философию правосудия. Предложенные подходы к пониманию философии права и правосудия основываются на принципах: правопонимания; соотношения и различения понятий «право» и «закон»; разграничения сущего и должного; определенного философского понимания права; понимания философии как науки о закономерностях; поиске смыслов. Предложенные понимания философии правосудия как прикладной философии права, которые могут быть расширены, обнаруживают ключевые смыслы философского осмысления правосудия в контексте философии права. Ключевые слова: философия права, философия правосудия, философии как наука, правопонимание, право и закон, сущее и должное, философское понимание права, поиск смыслов права. The philosophical reasoning about justice as judicial process is methodologically outlined through the reasoning thereabout as an applied philosophy of law. The basis for the offered approaches to reasoning about the philosophy of justice forms a particular concept of the philosophy of law, which, accordingly, forms a certain philosophy of justice. The presented approaches are based on such principles or criteria as: a concept of law (праворозуміння); correlations and distinctions between the concepts of «right» (Recht) and «law» (Gesetz); differentiating between the fact (what is) and value (should be); a certain philosophical comprehension of law; the paradigm considering philosophy as a science about conformities of the law; the search for meanings. Various understandings of the philosophy of justice as the applied philosophy of law, which are not limited to the ones listed, unfolds key meanings of the philosophical reasoning about justice in the context of the philosophy of law. Key words: philosophy of law, philosophy of justice as judicial process, philosophy as science, positivist and natural law concepts of law, law as fact and value, philosophical concept of law, search of senses of law.